Changes in residential land-use of Tripoli city, Libya: 1969-2005 - Osama Kh Ali,; Noorazuan Hashim,; Katiman Rostam,; Hamzah Jusoh, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
This article focuses on the pattern of residential land use changes in the city of Tripoli which had been much affected by rapid urbanization in recent decades, especially within the period 1969 – 2005. The city comprises seven mahalas or zones, namely, Andalus, Sogaljumaa, Bosleam, Central Tripoli, Ainzara, Tajura and Janzur. This analysis involved all the seven mahalas and was facilitated by the utilisation of GIS land use maps and digital satellite imageries. In 1980s, the Libyan government introduced a comprehensive plan for the Tripoli city comprising a housing scheme to be implemented until 2000. During the first phase of the plan implementation (1970-1980 ) high urbanization rates and in-migration to the city centre and its vicinity had led to the expansion of residential land uses at the expense of other land uses. Thus, residential land use pattern in the mahalas near central Tripoli had undergone dramatic transformations during this period. In contrast, the second phase (1981-1992) had witnessed a slower pace of growth in residential development due to the lack of financial support. Even more recently (2000-2005), constraints in the supply of building materials and relatively high costs of labour had been the most significant factors in slowing down the pace of residential development in the city